Goltz syndrome (focal dermal hypoplasia) and webbed neck. Case report of a very rare association. - Serdar, Z.A.; Gönenç, I.G.; Yaşar, Ş; Doruk, T.; Güneş, P.; Akici, N. (European Journal of Pediatric Dermatology, 2011)
Focal dermal hypoplasia (FDH) also known as Goltz syndrome or Goltz-Gorlin syndrome, is a rare genetic skin disorder originating both from mesodermal and ectodermal tissues and resulting in malformations of many organs such as eyes, skeletal and central nervous system, teeth and mainly the skin and its appendages, hair and nails. Here is reported a seven year old girl with FDH presenting webbed neck, a very rare finding of the syndrome. A large number of generalized, hypopigmented, atrophic linear and reticular macules of various size following the Blaschko's lines on the patient's entire skin surface and adipose tissue herniation on deltoid regions of both upper extremities and abdominal wall, syndactyly of the third and fourth fingers on the left hand, claw finger deformity of the right hand and hypoplasia and dystrophy of the nails were observed. Histopathological findings were consistent with FDH.